Patellar tendon versus hamstring tendon autograft for anterior cruciate ligament rupture in adults - Mohtadi, Nicholas GH (Cochrane Database Syst Rev, 2011)
BACKGROUND: Reconstruction of the anterior cruciate ligament (ACL) commonly involves patellar tendon (PT) or hamstring tendon(s) (HT) autografts. There is no consensus with respect to the choice between these two grafts in ACL surgery. OBJECTIVES: This review compared the outcomes of ACL reconstruction using PT versus HT autografts in ACL deficient patients. SEARCH METHODS: We searched the Cochrane Bone, Joint and Muscle Trauma Group Specialised Register (April 2008), the Cochrane Central Register of Controlled Trials (2008, Issue 2), MEDLINE (1966 to April 10 2008), EMBASE (1980 to April 10 2008), conference proceedings and reference lists. No language restrictions were applied. SELECTION CRITERIA: Randomized and quasi‐randomized controlled trials comparing outcomes (minimum two year follow‐up) following ACL reconstruction using either PT or HT autografts in skeletally mature adults, irrespective of the number of bundles, fixation method or incision technique. DATA COLLECTION AND ANALYSIS: After independent study selection, the four authors independently assessed trial quality and risk of bias, and extracted data using pre‐developed forms. Trial authors were contacted for additional data and information. Risk ratios with 95% confidence intervals were calculated for dichotomous outcomes, and mean differences and 95% confidence intervals for continuous outcomes. MAIN RESULTS: Nineteen trials providing outcome data for 1597 young to middle‐aged adults were included. Many trials were at high risk of bias reflecting inadequate methods of randomization, lack of blinding and incomplete assessment of outcome. Pooled data for primary outcomes, reported in a minority of trials, showed no statistically significant differences between the two graft choices for functional assessment (single leg hop test), return to activity, Tegner and Lysholm scores, and subjective measures of outcome. There were also no differences found between the two interventions for re‐rupture or International Knee Documentation Committee scores. There were inadequate long‐term results, such as to assess the development of osteoarthritis. All tests (instrumental, Lachman, pivot shift) for static stability consistently showed that PT reconstruction resulted in a more statically stable knee compared with HT reconstruction. Conversely, patients experienced more anterior knee problems, especially with kneeling, after PT reconstruction. PT reconstructions resulted in a statistically significant loss of extension range of motion and a trend towards loss of knee extension strength. HT reconstructions demonstrated a trend towards loss of flexion range of motion and a statistically significant loss of knee flexion strength. The clinical importance of the above range of motion losses is unclear. AUTHORS' CONCLUSIONS: There is insufficient evidence to draw conclusions on differences between the two grafts for long‐term functional outcome. While PT reconstructions are more likely to result in statically stable knees, they are also associated with more anterior knee problems.